First ionospheric experimental campaign and observation at Fraser's Hill, Malaysia: total electron content (TEC) and scintillation measurements - Zain, A.F.M; Ho, Yih Hwa; Abdullah, M; Rhazali, Z.A; Abdullah, S; Marsimin, M.F (2005)
The ionosphere over Malaysia is unique because of her location near the equator where the existence of the equatorial anomaly, electrojet, and fountain effect have made it good for studies. As part of a rejuvenation process in investigating the equatorial ionosphere in Malaysia, a short duration ionospheric experimental campaign was carried out at Fraser's Hill (lat. 3° 42.9' N, long. 101° 44.2' E, at an altitude of 1298 m) from GPS Week 1334 to 1335 (Jul 31, 2005 - Aug 13, 2005. This paper presents the results of the TEC and scintillation measurements obtained from the GPS receiver. TEC is a measure of the number of electrons along the path from the satellite and is reported as TEC units (1 TECU = 1 × 1016 electrons). The number is proportional to the ionospheric delay between the L1 and L2 signals. However, amplitude scintillation monitoring is traditionally accomplished by monitoring index S4 derived from signal intensity of signals received from satellites.